Spherical Micro/Nano Hierarchical Structures for Energy and Water Harvesting Devices. Issue 7 (4th May 2022) - Jung, Young; Ahn, Junseong; Kim, Ji‐Seok; Ha, Ji‐Hwan; Shim, Jaehwan; Cho, Hanchul; Oh, Yong Suk; Yoon, Yong‐Jin; Nam, Youngsuk; Oh, Il‐Kwon; Jeong, Jun‐Ho; Park, Inkyu
Abstract: Three‐dimensional (3D) hierarchical structures have been explored for various applications owing to the synergistic effects of micro‐ and nanostructures. However, the development of spherical micro/nano hierarchical structures (S‐HSs), which can be used as energy/water harvesting systems and sensing devices, remains challenging owing to the trade‐off between structural complexity and fabrication difficulty. This paper presents a new strategy for facile, scalable S‐HS fabrication using a thermal expansion of microspheres and nanopatterned structures. When a specific temperature is applied to a composite film of microspheres and elastomers with nanopatterned surfaces, microspheres are expanded and 3D spherical microstructures are generated. Various nanopatterns and densities of spherical microstructures can thereby be quantitatively controlled. The fabricated S‐HSs have been used in renewable electrical energy harvesting and sustainable water management applications. Compared to a triboelectric nanogenerator (TENG) with bare film, the S‐HS‐based TENG exhibited 4.48 times higher triboelectric performance with high mechanical durability. Furthermore, an S‐HS is used as a water harvesting device to capture water in a fog environment. The water collection rate is dramatically enhanced by the increased surface area and locally concentrated vapor diffusion flux due to the spherical microstructures. Abstract : A new strategy for the facile and scalable fabrication of spherical micro/nano hierarchical structures (S‐HSs) is proposed by combining the nanopatterned structures and expandable microspheres. This S‐HS, which enables the control of nanopatterns and the density of spherical microstructures, dramatically increases the surface area and roughness. Effective electrical energy and water harvesting devices are realized using these S‐HSs.